Zastosowanie drzew klasyfikacyjnych do oceny poziomu świadczeń emerytalnych z różnych typów systemów - Jajko-Siwek, Alicja (Studia Oeconomica Posnaniensia, 2013)
Pension systems worldwide operate according to a variety of solutions, but every system, regardless of its type, should meet the same basic social goal, which is to provide an adequate income aft er retirement. Research has shown that the classifi cation tree method is extremely useful in evaluating how to achieve this objective. Th is paper provides simulations of pension benefi ts, and by assessing their level using classifi cation trees it enabled the identification of differences between the DB and NDC pension systems. In addition, the use of classifi cation trees made it possible to identify the factors that play a key role with regard to the level of future retirement benefits in the systems analysed and from a notional defi ned contribution system.